The effect of microglial ablation and mesenchymal stem cell transplantation on a cuprizone‐induced demyelination model. Issue 5 (29th September 2020) - Tahmasebi, Fatemeh; Pasbakhsh, Parichehr; Barati, Shirin; Madadi, Soheila; Kashani, Iraj R.
Abstract: Multiple sclerosis (MS) is a demyelinating autoimmune disease of the central nervous system with symptoms such as neuroinflammation, astrocytosis, microgliosis, and axonal degeneration. Mesenchymal stem cells (MSCs) with their immunomodulation, differentiation, and neuroprotection abilities can influence the remyelination process. The goal of this study is to investigate the impact of microglial ablation and MSCs transplantation on remyelination processes in the corpus callosum (CC) of the cuprizone demyelination model. For the induction of a chronic demyelination model, C57BL6 mice were fed with chow containing 0.2% cuprizone (wt/wt) for 12 weeks. For the depletion of microglia, PLX3397 was used as a colony‐stimulating factor 1 receptor inhibitor for 21 days. MSCs were injected to the right lateral ventricle and after 2 weeks, the mice were killed. We assessed glial cells using specific markers such as APC, Iba‐1, and GFAP using the immunohistochemistry method. Remyelination was evaluated by Luxol fast blue (LFB) staining and transmission electron microscope (TEM). The specific genes of microglia and MSCs were evaluated by a quantitative real‐time polymerase chain reaction. According to the results of the study, 21 days of PLX3397 treatment significantly reduced microglial cells, and MSCs transplantation decreased the number of astrocytes, whereas the oligodendrocytes population increased significantly in PLX + MSC group in comparison with the cuprizone mice. Furthermore, PLX and MSC treatment elevated levels of remyelination compared with the cuprizone group, as confirmed by LFB staining and TEM analysis. The molecular results showed that MSC transplantation significantly decreased the number of microglia through the CX3CL1/CX3CR1 axis. These results revealed that PLX3397 treatment and MSCs injection reduced microgliosis and astrocytosis. It also increased the oligodendrocytes population by enhancing remyelination in the CC of the cuprizone model of MS. Abstract : Cell therapy with microglial ablation could significantly improve chronic demyelination in neurodegenerative diseases. Hence, by understanding the mechanisms involved in the activation and proliferation of oligodendrocytes by mesenchymal stem cells, trophic factors can yield promising results.